OPERASI-OPERASI MILITER DI PAPUA PAGAR MAKAN TANAMAN? - al Rahab, Amiruddin (Jurnal Penelitian Politik, 2006)
The aim of this paper is to describe military operations in Papua undertaken by Kodam Tjendrawasih. The operations conducted by the Kodam based on security approach have caused thousands of civilian victims. Therefore, Kodam that suppose to be the protector of the people and the State has triggered bigger problem for unity of the nations, separating movement in the region. The problem of Papua has to be solved by targeting the roots of the problem, which is the role of military as a tool for solving conflict in Papua. After all, the main problem in Papua has to be identified and solved by an approach that reaches the basic problem in that region: self esteem and the welfare of the people of Papua.